An analysis of participatory decision making and job satisfaction of administrative staff at international Islamic tertiary institution - Salleh, Mohamad Johdi; Al-Daba, Abdulmajid (Public Knowledge Project, 2014)
The aim of this study is to examine a participative decision making and job satisfaction of administrative staff at International Islamic Tertiary Institution according to their background. The study utilized a descriptive survey research method which involved 255 administrative staff of academic faculties, centers, divisions and offices of the International Islamic University Malaysia (IIUM), Kuala Lumpur. The finding shows that the average mean score to all the 6 items is 3.24 and standard deviation is 0.759 which indicate that most of the staff was satisfied with the general working condition of the institution. Secondly, the overall mean score to all the 8 items is 3.58 (SD 0.855) indicating that majority of the staff was satisfied with the offered salary package. Finally, the overall mean score to all the 8 items is 3.69 (SD 0.742) indicating that the staff was satisfied with the job design and feedback mechanism operated at IIUM. The study shows that the involvement of staff in decision-making process enhances effectiveness and legitimacy of such decisions, and boosts employees’ morale and productivity.